Citizenship and immigration - Joppke, Christian (Immigration & society., 2010)
"This book provides a succinct overview of the new academic field of citizenship and immigration, as well as presenting a fresh and original argument about changing citizenship in our contemporary human rights era." "Instead of being nationally resilient or in postnational decline, citizenship in Western states has continued to evolve, converging on a liberal model of inclusive citizenship with diminished rights implications and increasingly universalistic identities. This convergence is demonstrated through a sustained comparison of developments in North America, Western Europe, and Australia. Topics covered in the book include: recent trends in nationality laws; what ethnic diversity does to social citizenship; the decline of multiculturalism yet continuing rise of antidiscrimination policies; and the new state campaigns to upgrade and renationalize citizenship in the post-2001 period."--book jacket.